Pedagogic Interpretation of Civil Identity Concept - EFIMENKO, Veronika Nikolaevna; STAFEEVA, Yulia Valerievna (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
The article considers approaches to revealing the notion of civil identity and analyzes the components of this phenomenon from the viewpoint of pedagogy.